1966
DOI: 10.1103/physrev.150.146
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Spin Dependence of theHe3(n, p)TReaction and of the Nuclear Susceptibility of Adsorbed

Abstract: The spin dependence of the He z (n,p)T reaction was investigated by studying the transmission of polarized thermal neutrons through a polarized He 3 target which consisted of He 3 adsorbed on zeolite. It was found that the interaction cross section was essentially all associated with an I~ J=0 channel, i.e., Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
2

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 19 publications
0
58
0
2
Order By: Relevance
“…This indicates that, for given values of P n and ∆σ, the figure of merit for comparing polarized targets in transmission experiments should be τ 2 P 2 t . The figure of merit for the TUNL solid 3 He target exceeds current polarized 3 He gas targets by nearly two orders of magnitude. Furthermore, the densities of the condensed phases of 3 He correspond to nearly 100 MPa of room temperature gas, while targets of polarized 3 He gas are limited to 1 MPa.…”
Section: Experimental Apparatus a Polarized 3 He Targetmentioning
confidence: 86%
See 2 more Smart Citations
“…This indicates that, for given values of P n and ∆σ, the figure of merit for comparing polarized targets in transmission experiments should be τ 2 P 2 t . The figure of merit for the TUNL solid 3 He target exceeds current polarized 3 He gas targets by nearly two orders of magnitude. Furthermore, the densities of the condensed phases of 3 He correspond to nearly 100 MPa of room temperature gas, while targets of polarized 3 He gas are limited to 1 MPa.…”
Section: Experimental Apparatus a Polarized 3 He Targetmentioning
confidence: 86%
“…Owing to the low intensity of the polarized neutron beam, an extremely thick sample of polarized 3 He is desirable. In a measurement of the neutron transmission asymmetry ε, the number of observed neutron counts N necessary to obtain a statistical precision ∆ε/ε is…”
Section: Experimental Apparatus a Polarized 3 He Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…P (5) have shown that the thermal 3~e ( n ,~)~ cross section is essentially all associated with a J = 0 state of the compound system, which means that u p = -oo. The transmission flipping ratio is then 2Ntfnao RT = e which is very convenient for nuclear polarization determination.…”
Section: The Transmission Of Neutrons Through the Unpolarized Sample mentioning
confidence: 99%
“…which has a much larger cross section when the n− 3 He have a total spin J = 0 compared to J = 1 [8]. In a magnetic field B 0 , the UCN and 3 He spins will precess at their respective Larmor frequencies: ω n = γ n B 0 and ω 3 = γ 3 B 0 , where γ i is the gyromagnetic ratio of each species.…”
mentioning
confidence: 99%